Associations of Training and Academic Stress with Sleep in Dual-Career Collegiate Badminton Athletes: A Preliminary Study - Wang H; Dai Y; Li X; Yu L (Nature and Science of Sleep, 2024)
Haonan Wang,1,2 Yinghong Dai,3 Xiaotian Li,2,4 Liang Yu1 1Department of Exercise Physiology, School of Sport Science, Beijing Sport University, Beijing, 100084, People’s Republic of China; 2Department of Physical Education and Research, Central South University, Changsha, 410083, People’s Republic of China; 3Xiangya School of Medicine, Central South University, Changsha, 410008, People’s Republic of China; 4School of Sport Training, Wuhan Sports University, Wuhan, Hubei, 430079, People’s Republic of ChinaCorrespondence: Xiaotian Li, Department of Physical Education and Research, Central South University, Changsha, 410083, People’s Republic of China, Tel +86 18975197870, Fax +86 731 88876141, Email xiaotianli@csu.edu.cn Liang Yu, Department of Exercise Physiology, School of Sport Science, Beijing Sport University, Beijing, 100084, People’s Republic of China, Tel/Fax +86 1062967640, Email yuliang@bsu.edu.cnIntroduction: Poor sleep negatively impacts cognitive and physical functioning and affects athletic and academic achievement. “Dual-career” athletes emphasize the pursuit of academic excellence along with athletic performance.Purpose: The study aimed to assess sleep characteristics and sleep quality in dual-career collegiate badminton athletes. Furthermore, the study explored associations between training and academic stress and sleep, providing a theoretical basis for better training and sleep programs for dual-career athletes.Participants and Methods: In this study, 15 dual-career collegiate badminton athletes were recruited, and 12 subjects (male n = 8, female n = 4, mean age 20.3 ± 1.7) completed the questionnaire. Repeated measurements were taken monthly in the spring semester from March to August 2021. The questionnaire assessed sleep quality and daytime sleepiness by the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Score (ESS). Moreover, we collected average training, study time per week, and monthly sports competitions and academic tests to quantify participants’ training and academic stress.Results: An average of 36.1% of dual-career athletes reported poor sleep and 25.0% had excessive daytime sleepiness. Overall, a significant positive correlation existed between PSQI scores and weekly study hours (r = 0.308, p = 0.009). Significant positive correlations were found between the four stressors and PSQI (August: r = 0.868, p < 0.001; July: r = 0.573, p = 0.026) or ESS scores (March: r = − 0.678, p = 0.015; August: r = 0.598, p = 0.040) for specific months. Hierarchical linear modeling (HLM) analysis identified that lower study and training hours predict better sleep quality.Conclusion: Dual-career collegiate badminton athletes had a higher prevalence of poor sleep and daytime sleepiness, and daytime sleepiness did not result in better sleep quality; study and training hours had the greatest effect on the sleep quality of dual-career collegiate badminton athletes.Keywords: training stress, academic stress, dual-career collegiate athletes, sleep quality, subjective evaluation